Steady state security assessment of power system using fuzzy technique - Khairuddin, Azhar (Penerbit UTM, 2007)
Cheap but reliable supply of electrical energy is a crucial factor for the survival of the modern society and all sorts of its development activities. With increased demand for electricity in the countries like Malaysia which are undergoing rapid industrialization and urbanization, the utilities are growing in size through interconnection to the generators of the emerging Independent Power Producers (IPPs) on top of the utility owned power stations. However, this has resulted in a task more difficult than ever before, to ensure two conflicting interests i.e. system security (reliability) and economy. Depending upon the situation, security may override economic considerations.